(3JQLeI YhV Hf eMeO Hf SGde HGaVds - (3eMeO Hf YhV Hf eMeO Hf SGde HGaVd, HGaVd,J (B1340 (3g` s ((3eMeO Hf YhV Hf eMeO Hf SGde HGaVd s)
(3ChdgG (B:s
(3SjOj hCHj cGf ehdOg HJQje ai TgQ Pi GdbYOI SfI (B1265(3g` s
(3BNQgG (B:s
(3hbO QDjJ dg HYO haGJg GdeQGAi GdMSfIGfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B304 - (3U(B326s
(3cJHgG hdOg eMeO ef cJGH UdI GdCgd aj efGbH Bd HGaVds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B320s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B109 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(565 (3c(B) s
Keywords: (3GdJGQjNs